Impact of Cognitive Reserve and Structural Connectivity on Cognitive Performance in Multiple Sclerosis - Lopez-Soley, Elisabet; Solana, Elisabeth; Martínez-Heras, Eloy; Andorra, Magi; Radua, Joaquim; Prats-Uribe, Albert; Montejo, Carmen; Sola-Valls, Nuria; Sepulveda, Maria; Pulido-Valdeolivas, Irene; Blanco, Yolanda; Martinez-Lapiscina, Elena H.; et al. (Frontiers in Neurology, 2020)
Background: Cognitive reserve (CR) could attenuate the impact of the brain burden on the cognition in people with MS (PwMS). Objective: To explore the relationship between CR and structural brain connectivity, and investigate their role on cognition in PwMS cognitively impaired (PwMS-CI) and cognitively preserved (PwMS-CP). Methods: In this study, 181 PwMS (71% female; 42.9±10.0 years) were evaluated using the Cognitive Reserve Questionnaire (CRQ), Brief Repeatable Battery of Neuropsychological tests and MRI. Brain lesion and gray matter volumes were quantified, as was the structural network connectivity. Patients were classified as PwMS-CI (z-scores -1.5 SD in at least two tests) or PwMS-CP. Linear and multiple regression analyses were run to evaluate the association of CRQ and structural connectivity with cognition in each group. Hedges’s effect size was used to compute the strength of associations. Results: We found a very low association between CRQ scores and connectivity metrics in PwMS-CP while in PwMS-CI this relation was low-to-moderate. The multiple regression model, adjusted for age, gender, mood, lesion volume and graphs metrics (local and global efficiency, and transitivity), indicated that the CRQ [β=0.26, 95% CI (0.17-0.35)] was associated with cognition (adjR2=0.34) in PwMS-CP (55%). In PwMS-CI, CRQ [β=0.18, 95% CI (0.07-0.29)], age, and network global efficiency were independently associated with cognition (adjR2=0.55). The age and gender adjusted association between CRQ score and global efficiency on having an impaired cognitive status was -0.338 (OR: 0.71, p = 0.036) and -0.531 (OR: 0.59, p = 0.002), respectively. Conclusions: CR seems to have a marginally significant effect on brain structural connectivity, observed in patients with more severe clinical impairment. It protects PwMS from cognitive decline regardless of their cognitive status, yet once cognitive impairment has set in, brain damage and aging are also influencing cognitive performance.